Elements for a Chronology of Galician Literature (1801-1900) - López, Teresa (Madrygal. Revista de Estudios Gallegos, 2015)
The aim of this presentation is to describe the research project CROLIGA, A Chronology of Galician Literature (1801-1900). This project intends to build an extensive database of works published in the 19th century and make it publicly available online. The presentation will be particularly concerned with the characteristics, stages of development and current results of this project.
Keywords: Chronology; Galician literature; 19th century; CROLIGA